Ultrastructural and developmental toxicity of potato and tomato leaf extracts to beet armyworm, Spodoptera exigua (lepidoptera: noctuidae). Issue 10 (21st July 2016) - Adamski, Zbigniew; Radtke, Katarzyna; Kopiczko, Agnieszka; Chowański, Szymon; Marciniak, Paweł; Szymczak, Monika; Spochacz, Marta; Falabella, Patrizia; Lelario, Filomena; Scrano, Laura; Bufo, Sabino A.
Abstract: Beet Armyworm, Spodoptera exigua is a herbivorous moth and a serious pest of many economically important plants, which are used as food sources. Because of rigorous standards of food quality, usage of synthetic insecticides in crop protection, against pests, is limited. Solanaceae plant extracts may be a relatively cheap source of efficient natural insecticides that can limit usage of synthetic substances. Their biological activity is not fully known. In particular, ultrastructural studies, using transmission electron microscopy, are not usual. In the present article we describe the effects of sublethal concentrations of tomato and potato leaf extracts against S. exigua . Acute lethal effects were not observed. Both extracts exerted similar effects within midgut and fat body cells. Midgut cells were not significantly altered while fat body cells showed prominent swelling of nuclear envelope and endoplasmic reticulum, vacuolization of mitochondria and fusion of fat droplets. These changes were much more intensive within groups exposed to potato than tomato extracts at highest concentration at least. Light microscopy was used to observe and document developmental alterations of S. exigua exposed to potato and tomato leaf extracts. Potato leaf extracts significantly decreased hatching success and caused morphological malformations of imagoes. Among them, malformations of wings were the most prominent. Interestingly, these effects were not observed within populations exposed to tomato extracts at highest concentration at least.